2006
DOI: 10.1080/15622970510029957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olanzapine treatment on platelet glutamine synthetase-like protein and glutamate dehydrogenase immunoreactivity in schizophrenia

Abstract: According to contemporary views, the glutamatergic system is implicated in the pathogenesis of schizophrenia, and atypical neuroleptics exert their effects (at least partially) through the glutamatergic system. Immunoreactive glutamate-metabolising enzymes, such as glutamine synthetase-like protein (GSLP) and two glutamate dehydrogenase isoenzymes (GDH), have been discovered in human platelets. The amount of GSLP in the platelets of 40 chronic patients with schizophrenia was found to be significantly higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
0
4
0
3
Order By: Relevance
“…Transcription studies have demonstrated alterations in proteins involved in the binding and transmission of glutamate within the thalamus, including those which interact with the NMDA receptor (Bruneau et al, 2005). Proteins for the degradation and transport of breakdown products of glutamate have also been suggested to be up-regulated within the thalamus, including glutamine synthase (GS), vesicular glutamate transporter (VGLUT), phosphoprotein associated with glycosphingolipidenriched microdomains (PAG), excitatory amino-acid transporters (EAAT) 1 and 2 (Bruneau et al, 2005), glutamine-synthase-like protein (GSLP) and glutamate dehydrogenase (GDH) (Burbaeva et al, 2006). Glutamine, the breakdown product of glutamate, has been shown to be increased within the thalamus in both antipsychotic naïve and chronically medicated patients (Theberge et al, 2003).…”
Section: Nmda Receptor Hypofunctionmentioning
confidence: 99%
“…Transcription studies have demonstrated alterations in proteins involved in the binding and transmission of glutamate within the thalamus, including those which interact with the NMDA receptor (Bruneau et al, 2005). Proteins for the degradation and transport of breakdown products of glutamate have also been suggested to be up-regulated within the thalamus, including glutamine synthase (GS), vesicular glutamate transporter (VGLUT), phosphoprotein associated with glycosphingolipidenriched microdomains (PAG), excitatory amino-acid transporters (EAAT) 1 and 2 (Bruneau et al, 2005), glutamine-synthase-like protein (GSLP) and glutamate dehydrogenase (GDH) (Burbaeva et al, 2006). Glutamine, the breakdown product of glutamate, has been shown to be increased within the thalamus in both antipsychotic naïve and chronically medicated patients (Theberge et al, 2003).…”
Section: Nmda Receptor Hypofunctionmentioning
confidence: 99%
“…Studies measuring glutamine synthetase protein levels in the brain do not find changes that can be related to antipsychotic treatment (Burbaeva et al, 2003, Toro et al, 2006. However, recently it was reported that peripheral protein levels of GSLP, an isoform of glutamine synthetase, may be altered by treatment with antipsychotics (Burbaeva et al, 2006). Burbaeva and colleagues demonstrated that increased platelet expression of GSLP in schizophrenia is reduced following treatment with the atypical antipsychotic, olanzapine.…”
Section: Effects Of Haloperidol On Expression Of Glutamine Synthetasementioning
confidence: 99%
“…So, our special attention was paid to the treatment efficiency (clinical response) evaluation in the patients. In our previous study, when searching for biochemical predictor of pharmacological therapy efficiency we have taken the decrease in PANSS total for positive treatment effect [26]. In the present work, we additionally regard PANSS positive, PANSS negative, PANSS psychopathological, NSA, and neurocognitive tests.…”
Section: Discussionmentioning
confidence: 99%